The conformation of enkephalin bound to its receptor: an “elusive goal” becoming reality - Sanfelice, Domenico; Temussi, Piero A. (Frontiers in Molecular Biosciences, 2014)
The availability of solid state structures of opioid receptors has prompted us to reconsider a crucial question concerning bioactive peptides: can their conformation be studied without any knowledge of the structure of their receptors? The meaning of this query depends mainly on the extreme conformational flexibility of small peptides, and amongst them the best known of bioactive peptides, enkephalin. All solution studies of enkephalin hint at an inextricable mixture of quasi isoenergetic conformers. In this study we refer to the only NMR work that yielded inter-residue NOEs, performed at very low temperature. We show that the conformers found in the equilibrium mixture at low temperature are indeed compatible with a good occupancy of the receptor active site.